2012
DOI: 10.3415/vcot-11-12-0189
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-operator variability associated with extracapsular suture tensioning

Abstract: Marked variation exists in the tension applied during fabello-tibial suture application, both within and between surgeons. This variation may lead to inconsistent clinical outcomes. Further studies are required to determine the clinical consequences of this marked variation in extracapsular suture tensioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It is our belief that LSS tensioning should aim to apply a tension that is only sufficient to limit cranial drawer but not excessive in order to limit its impact on 3D kinematics in the other planes. Variability associated with LSS tensioning has been reported within and between surgeons and is suggested to lead to inconsistent clinical outcomes [ 24 ]. Further studies are needed to assess the impact of excessive LSS suture tensioning on 3D kinematics in order to provide clearer clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…It is our belief that LSS tensioning should aim to apply a tension that is only sufficient to limit cranial drawer but not excessive in order to limit its impact on 3D kinematics in the other planes. Variability associated with LSS tensioning has been reported within and between surgeons and is suggested to lead to inconsistent clinical outcomes [ 24 ]. Further studies are needed to assess the impact of excessive LSS suture tensioning on 3D kinematics in order to provide clearer clinical guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…It thus appeared that with a similar surgical technique, inconsistent suture tensioning plays an important role in different postoperative stifle kinematics. A previous study also indicated that there is variability in the tension applied during ECS application, both within and between surgeons, which may lead to discrepancies in clinical outcomes [ 36 ]. Further studies are warranted to quantify the suture tension and assess the impact of different suture tensions.…”
Section: Discussionmentioning
confidence: 99%